Impact of Intermediate and Terminal Groups on the Thermal Stability of Bent-Core Liquid Crystals - Mohammed M. Aftan (Tikrit Journal of Pure Science)
A series of new mesogenic chalcone, azomethine and azo compounds were successfully synthesized. A chalcone was prepared via condensation of isophthaldehyde with a p-hydroxyacetophenone in a basic medium, Schiff bases was prepared by condensation isophthaldehyde with a p-hydroxyaniline in acidic medium. While azo compound was obtained by a reaction of m-diaminobenzen with NaNO2 and phenol, and the generated compound was reacted with alkyl bromide. The structures of such compounds were confirmed by FT-IR and 1H-NMR spectrometer. The liquid crystal phases were studied by Differential Scanning Calorimeter (DSC) and polarizing optical microscope with heating. A thermal stability of liquid crystal phases were increased by increasing the length of aliphatic chain to smectic phases and decreasing in the thermal stability of nematic phase. It has been observed that the thermal stability of liquid crystal in chalcone compounds were higher than others, azo and azomethine compound